Etnografando a batalha do vinho: uma análise da cena dos duelos de MCs face à estrutura social brasileira - Silva, Michael Guedes da (2020)
The expression “Batalha do Vinho (Battle of Wine)” names the meeting of young people from the North Zone of Natal with the form of dueling through rhymes. The contact with the event is based on prior knowledge of one of its organizers. To some extent, thanks to the active agency and strategies of this participant, the initiative experienced intense technical sophistication, receiving relevant artistic participation and seeing its audience grow significantly. The Batalha do Vinho, also showing itself as a favorable scenario for various debates, about violence, race and gender, for example, is constituting itself amidst solidarity and competition relations, always permeated by reality, but also by inevitable fictionalities. Spread across cities, states and countries, the practice of MC duels is evident as a cultural scene, characterized by informational excess and the instability of its incidences. The scene of battles is pertinent to hip-hop and maintains, in each of its geographic dimensions, places of congregation and paths that give cultural recognition and that show its pulse. In this city transit, the scene is articulated with different levels of economic activity. In such a way, this contact ends up giving greater elaboration to their incidences. The scenes, moreover, are also characterized as a juvenile and underground manifestation under anglophone influence – elements that make understanding more complex. In this scenario, the heated debates and the various experiences of professionalization can be synthesized, respectively, by the presence of elements of an externally legitimized knowledge – coming from the University and the political parties – and by a fierce competition to characterize the circuits of disputes that are gradually emerging – the state and regional selective and the national duel. Thus, The movement experienced by the scene makes possible to understand the Batalha do Vinho experience in two different moments: first, elaborated as a practice endowed with meanings and effects aimed at its participants and, in a second moment, as a credible opportunity for social ascension, either through competitions and other professional activities, or through political-militant engagement within the framework of the liberal democracy institutions. From these uses, it becomes possible to see, given the different treatments given to the country's social contingents, how the violence exerted in the territory and the largely ideological expectation of social inclusion complement each other in what I call the structuring process – to boost the scene’s adhesion, in coherence with hip-hop itself, to current social forms. It is a process similar to the one experienced, although at different stages, by related cultural expressions and their practices. In such a way, the structuring process reifying a social text that, interested, is collectively shared; a text that, before portraying the social experience, is reaffirmed with a view to stimulating the deepening of structural relations – the neoliberalism and its perverse globalization. Finally, a constant presence throughout the experience portrayed is the internet, precisely online social networks. Whether as a space for uninterrupted sociability or as a means of publicize events, whether in denouncing aggressions suffered or in building expectations for success, the uses of internet became essential.